The Role of KRAS in Macropinocytosis and its Implications of Multi-Drug Resistance in Cancer - Fenyvesi, Ferenc; Ibrahim, Zeinab (De Remediis, 2024)
KRAS is one of the most frequently mutated oncogenes in cancer and is involved in various tumorigenic processes. Among its diverse roles, KRAS mutations have been shown to upregulate macropinocytosis, a form of endocytosis that allows cells to engulf extracellular fluid and its contained solutes, subsequently supporting the increased need for cancer cells’ growth and proliferation. The nutrient uptake function of macropinocytosis was initially described within the framework of KRAS-driven pancreatic tumors. Although constitutive macropinocytosis can be induced by activating mutations of proteins that are commonly found in cancer, KRAS-induced macropinocytosis constitutes a fundamental area of research due to the high occurrence of mutated KRAS in cancer ( 1/3 of all cancers). Furthermore, KRAS-mutated macropinocytosis not only contributes to tumorigenesis but also plays a critical role in developing resistance to treatments, as it was found to be implicated in Multi-Drug Resistance (MDR) in cancer cells. This mini-review aims to synthesize current knowledge of mechanisms of KRAS-mutated macropinocytosis briefly and examines the relationship between KRAS and macropinocytosis in the light of its role in cancer progression and drug resistance, highlighting therapeutic implications, targeting potential vulnerabilities and outlining clinical advancements in pertinent therapies.